2022
DOI: 10.1002/fsn3.3055
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative prevalence of Escherichia coliO157 in different food samples using real‐time qPCR method

Abstract: Escherichia coli serogroup O157 is the main causative agent of several intestinal and extra‐intestinal foodborne diseases in humans through consumption of low‐dose contaminated foods such as milk, beef, and vegetables. To date, studies regarding the quantitative prevalence of E. coli O157 in foods are so limited. Therefore, this study aimed to evaluate the quantitative prevalence rate of E. coli serogroup O157 in raw milk (n = 144), vegetable salad (n = 174), and minced beef samples (n = 108) using the real‐ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 43 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…It may also occur when a toxigenic food borne or waterborne pathogen establishes itself in a food or water supply and produces different intestinal and extra-intestinal toxins which are ingested . The experimental studies regarding the quantitative prevalence of E. coli O157 in foods are so limited [159]. Therefore, this study reported by [159] evaluated the quantitative prevalence rate of E. coli serogroup O157 in raw milk (n = 144), vegetable salad (n = 174), and minced beef samples (n = 108) using the real-time qPCR SYBR green melting curve method targeting the rfbA gene [159].…”
Section: E Coli Detection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It may also occur when a toxigenic food borne or waterborne pathogen establishes itself in a food or water supply and produces different intestinal and extra-intestinal toxins which are ingested . The experimental studies regarding the quantitative prevalence of E. coli O157 in foods are so limited [159]. Therefore, this study reported by [159] evaluated the quantitative prevalence rate of E. coli serogroup O157 in raw milk (n = 144), vegetable salad (n = 174), and minced beef samples (n = 108) using the real-time qPCR SYBR green melting curve method targeting the rfbA gene [159].…”
Section: E Coli Detection Methodsmentioning
confidence: 99%
“…There have also been illnesses in British Columbia, Alberta, Ontario, Prince Edward Island, New Brunswick, Nova Scotia, and Newfoundland and Labrador [157]. The majority of people who became sick are children aged five and younger and adults aged 65 and older [157][158][159][160][161][162][163][164][165][166][167].…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial pathogenicity is defined as the ability of bacterial strains to induce infection, release toxins, produce virulence and cause diseases and mortality in the host (humans). All bacterial pathogens have pathogenicity activity [24]. Specific mechanisms mediate this ability between bacterial pathogens and human host cells.…”
Section: Bacterial Pathogenicity Definitionmentioning
confidence: 99%
“…They are two common pathogenic bacteria that can cause infections in humans. Additionally, they are prevalent foodborne pathogens that are capable of causing food poisoning [21]. Given the described facts, this study is aimed at assessing the growth-inhibiting potential of an EE solution derived from papaya, pineapple, and Kasturi orange fruits against pathogenic bacteria Escherichia coli and Staphylococcus aureus.…”
Section: Introductionmentioning
confidence: 99%